A complication probability planning study to predict the safety of a new protocol for intracranial tumour radiotherapy in dogs. (31st August 2016) - Rohrer Bley, C.; Meier, V.; Schwarz, P.; Roos, M.; Besserer, J.
Abstract: Technical advances make it possible to deliver radiation therapy for canine intracranial tumours in fewer fractions, under the assumption of equivalent tumour control. With the aim of estimating the late toxicity risk profile for various tumour sizes and locations, the present paper evaluates the normal tissue complication probability (NTCP) values for the intracranial organs at risk. By making isoeffect calculations, a new 10‐fraction radiation protocol was developed with the same tumour control probability (TCP) as a currently used 20‐fraction standard protocol, and complication risk profiles for brain, brainstem and optic chiasm were modelled using a representative population of 64 dogs with brain tumours. For >59% of cases, the new 10‐fraction protocol yielded an acceptable, low risk estimate of late toxicity (<10%). Our calculations suggest that it may be safe to treat small to intermediate‐sized tumours that are neither located near the optic chiasm nor at the brainstem with 10 daily fractions of 4.35 Gy.